Method for producing terephthalic acid and terephthalic acid produced therefrom

The process of alcoholysis and hydrolysis of waste polyesters using alcohols with four or more carbon atoms directly produces high-purity terephthalic acid, addressing environmental and cost issues associated with current methods.

JP2025511437AActive Publication Date: 2025-04-16SK CHEMICALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024547156
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2023-08-30
Publication Date
2025-04-16
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

Current methods for preparing terephthalic acid from waste polyesters often result in environmental pollutants, high process costs, and limited purity and yield due to the need for additional neutralization steps and high-pressure conditions.

Method used

A process involving alcoholysis of waste polyesters with alcohols having four or more carbon atoms, followed by hydrolysis, to directly produce solid terephthalic acid without additional neutralization steps, thereby reducing environmental impact and improving process efficiency.

Benefits of technology

This process enables the production of high-purity terephthalic acid with improved yield, reduces environmental pollutants, and lowers process costs by eliminating the need for high-pressure conditions and additional neutralization steps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511437000001
    Figure 2025511437000001
  • Figure 2025511437000002
    Figure 2025511437000002
  • Figure 2025511437000003
    Figure 2025511437000003
Patent Text Reader

Abstract

The present invention relates to a method for producing terephthalic acid in an environmentally friendly manner using waste polyester. In particular, according to one embodiment of the present invention, the method for producing terephthalic acid includes the steps of (1) subjecting waste polyester to alcoholysis using C4 or higher alcohol to produce a liquid composition containing the compound represented by formula 1, and (2) subjecting the liquid composition to hydrolysis, and thus can produce terephthalic acid in an environmentally friendly manner, improve processability, and reduce process costs.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Technical Field The present invention relates to a process for preparing terephthalic acid in an environmentally friendly manner using waste polyester and the regenerated terephthalic acid prepared thereby. [Background technology]

[0002] Background technology Due to its excellent mechanical strength, heat resistance, transparency and gas barrier properties, polyester is widely used as a material for beverage containers, packaging films, audio and video films, etc., or as an industrial material for medical fibers, tire cords, etc. In particular, polyester sheets or plates have good transparency and excellent mechanical strength, so they are widely used as raw materials for cases, boxes, partitions, shelves, panels, packaging materials, building materials, interior and exterior materials, etc.

[0003] Since waste plastics such as polyester are generated in unmanageable amounts worldwide every year, interest in recycling waste polyester or recycling processes using waste polyester is increasing. Furthermore, countries around the world are preparing regulations and plans for recycling waste plastic resources such as waste polyester. For example, regulations that require the use of recycled resins at a certain ratio or more in packaging materials used in various fields are being discussed.

[0004] In particular, polyethylene terephthalate (PET) has excellent properties in terms of heat resistance, processability, transparency and non-toxicity, and is therefore widely used in the manufacture of a wide range of products such as films, fibers, bottles and containers, etc. However, most of these are landfilled or incinerated after use, and therefore research into their reuse or regeneration processes is ongoing.

[0005] For example, Korean Patent Application Publication No. 1997-0042469 discloses a technique for preparing terephthalic acid by hydrolyzing waste polyethylene terephthalate with an aqueous alkaline solution to obtain a slurry of alkali metal salts and alkaline earth metal salts of terephthalic acid, which is then neutralized with an acid. As a result of the hydrolysis reaction, terephthalic acid salts are produced instead of terephthalic acid, and a neutralization step by adding an acid is required to convert it to terephthalic acid. There are problems with the resulting by-products generating environmental pollutants or generating a large amount of acid treatment waste liquid. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Korean Patent Application Publication No. 1997-0042469 Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, the present invention aims to provide a process for preparing terephthalic acid in an environmentally friendly manner by alcoholysis and hydrolysis of waste polyester using special alcohol, and the regenerated terephthalic acid prepared thereby. [Means for solving the problem]

[0008] A process for preparing terephthalic acid according to one embodiment of the present invention includes (1) subjecting waste polyester to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1, and (2) subjecting the liquid composition to hydrolysis. [ka]

[0009] In formula 1, R1 is an alkyl group having 4 or more carbon atoms.

[0010] Regenerated terephthalic acid according to another embodiment of the present invention is prepared by the process for preparing terephthalic acid described above and has a total metal content of less than 100 ppm as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0011] A polyester resin according to another embodiment of the invention includes recycled terephthalic acid. Effect of the Invention

[0012] In the process for preparing terephthalic acid according to one embodiment of the present invention, waste polyester is subjected to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition containing the compound represented by formula 1, which is then subjected to hydrolysis with water. Thus, terephthalic acid can be prepared in an environmentally friendly manner, and the process cost can be reduced and the processability can be improved.

[0013] In particular, in the process for preparing terephthalic acid according to one embodiment of the present invention, waste polyester is subjected to alcoholysis with a special alcohol, particularly an alcohol having 4 or more carbon atoms, to prepare a liquid composition containing the compound represented by formula 1, which is then subjected to hydrolysis with water. In the process for preparing terephthalic acid according to one embodiment of the present invention, solid terephthalic acid can be directly produced without additional steps, which is different from the conventional process in which terephthalic acid salt is produced from waste polyester and an additional step is carried out to neutralize it. Therefore, the process is not only easy to operate, but also reduces process costs and obtains excellent processability.

[0014] In addition, acids such as sulfuric acid or hydrochloric acid used to neutralize terephthalic acid salts have the problem of producing environmental pollutants such as Na2SO4 and NaCl as by-products or a large amount of acid treatment waste liquid. In contrast, the process for preparing terephthalic acid according to one embodiment of the present invention can directly produce solid terephthalic acid without additional neutralization step, unlike the conventional process, and is therefore environmentally friendly.

[0015] In addition, in the process for preparing terephthalic acid according to one embodiment of the present invention, the intermediate, i.e., the hydrolysis reaction product, is prepared in liquid form, so that the insoluble impurities such as metal catalysts and coloring pigments that may be contained in waste polyester, as well as additives such as soluble colorants, can be easily removed.Therefore, the purity and yield of the terephthalic acid produced by the simple process can be further improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below. The present invention is not limited to the disclosure shown below, and may be modified in various forms without departing from the spirit of the present invention.

[0017] Throughout this specification, when a part is referred to as "comprising" an element, it is to be understood that other elements may be included, rather than excluding other elements, unless specifically stated otherwise.

[0018] All numbers and expressions relating to quantities of ingredients, reaction conditions, and so forth used herein are understood to be modified by the term "about," unless otherwise indicated.

[0019] Throughout this specification, terms such as first, second, etc. are used to represent various components. However, these components are not limited by these terms. These terms are used only to distinguish one component from another.

[0020] A process for preparing terephthalic acid according to one embodiment of the present invention includes (1) subjecting waste polyester to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1, and (2) subjecting the liquid composition to hydrolysis. [ka]

[0021] In formula 1, R1 is an alkyl group having 4 or more carbon atoms.

[0022] In the conventional method of preparing terephthalic acid from waste polyester, solid terephthalic acid is obtained directly using an acid catalyst, or dimethyl terephthalate (DMT) or bis(2-hydroxyethyl) terephthalate (BHET) is produced as an intermediate by methanolysis or glycolysis, which is then converted to terephthalic acid. In such cases, terephthalic acid, dimethyl terephthalate, and bis(2-hydroxyethyl) terephthalate are all solids at room temperature or at relatively high temperatures.

[0023] When solid terephthalic acid is directly obtained using acid catalyst, the terephthalic acid precipitates as a solid immediately after formation, which makes it difficult to remove insoluble impurities or additives such as colorants and pigments that may be contained in waste polyester during the manufacturing process. Therefore, the improvement of purity or yield is limited. For this reason, a method is also used in which terephthalic acid salt is prepared from waste polyester and then neutralized to obtain solid terephthalic acid. In such a case, the purity and yield of terephthalic acid can be improved by removing insoluble impurities, but there is a problem that environmental pollutants such as Na2SO4 and NaCl as by-products or a large amount of acid treatment waste liquid is generated during the neutralization process of terephthalic acid salt.

[0024] Furthermore, when dimethyl terephthalate is prepared as an intermediate, a large amount of methanol needs to be used to produce dimethyl terephthalate. Therefore, very high pressure conditions are generated due to the methanol used, and further heating and high pressure processes are required to convert dimethyl terephthalate into a liquid phase to remove insoluble impurities, which reduces processability. Furthermore, when bis(2-hydroxyethyl) terephthalate is prepared as an intermediate, separation and recovery of ethylene glycol produced as a by-product during the manufacturing process is difficult, and therefore undesirable in terms of processability and process cost.

[0025] In addition, an environmentally friendly method is used to recycle waste polyester by adding metal salts to the waste polyester and directly hydrolyzing it with water. However, the processability is poor because it requires very high temperature conditions of over 300°C, and the reaction equipment must be able to withstand high pressures.

[0026] In contrast, in the process for preparing terephthalic acid according to one embodiment of the present invention, the intermediate, i.e., the hydrolysis reaction product, is prepared in liquid form, so that the insoluble impurities such as metal catalysts and coloring pigments that may be contained in waste polyester, as well as additives such as soluble colorants, can be easily removed.Therefore, the purity and yield of the produced terephthalic acid can be further improved.

[0027] Moreover, since solid terephthalic acid can be directly produced without an additional neutralization step, it is environmentally friendly and has excellent processability, unlike conventional processes. Furthermore, not only can ethylene glycol, which may be formed as a by-product during the preparation process, be easily separated and recovered, but also the alcohol having 4 or more carbon atoms used in the alcoholysis reaction can be easily separated and reused, resulting in excellent process cost reduction effects. Furthermore, the purification and transportation processes other than the reaction can be carried out at room temperature or low temperature, which further improves processability and economic efficiency.

[0028] For example, in the process of preparing terephthalic acid according to one embodiment of the present invention, waste polyester, alcohol having 4 or more carbon atoms and a very small amount of alcoholysis catalyst are first charged into a first high-pressure reactor, followed by alcoholysis reaction. The by-product ethylene glycol and unreacted alcohol (excess alcohol) formed during alcoholysis reaction can be recovered in a separate fractionation device after completion of the reaction and reused.

[0029] Furthermore, the ethylene glycol and unreacted alcohol formed during the reaction can be discharged in the form of a gas mixture immediately during the reaction, which is then condensed and recovered using an external cooling device. In such a case, the alcohol can be continuously fed to the high-pressure reactor at a volume and feed rate equal to the volume and discharge rate of the discharged gas mixture. Through a simple process such as fractional distillation or layer separation, the unreacted alcohol can be separated from the discharged gas mixture. The unreacted alcohol thus separated can be fed back to the first high-pressure reactor, from which the ethylene glycol can be recovered.

[0030] The liquid alcoholysis product obtained by the alcoholysis reaction can then be purified by cooling, adsorption and filtration. The purified alcoholysis reaction composition is fed into a second high-pressure reactor together with water to carry out the hydrolysis reaction, and then a slurry-type solution is obtained, which is filtered to obtain solid terephthalic acid. In such a case, a small amount of hydrolysis catalyst can be further fed together with water before the hydrolysis reaction. The hydrolysis catalyst can be the same as or different from the alcoholysis catalyst.

[0031] Furthermore, after completion of the hydrolysis reaction, the unreacted components can be recovered and reintroduced into the alcoholysis or hydrolysis reaction for one or more reactions, thereby improving the yield of the terephthalic acid finally produced. Furthermore, the amount of waste generated can be reduced, thereby being environmentally friendly. For example, the filtrate obtained by filtering the excess unreacted alcohol (having 4 or more carbon atoms) and ethylene glycol as a by-product using a filter or the like can be reintroduced into the hydrolysis reaction.

[0032] Process for preparing terephthalic acid A process for preparing terephthalic acid according to one embodiment of the present invention includes (1) subjecting waste polyester to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1, and (2) subjecting the liquid composition to hydrolysis. [ka]

[0033] In formula 1, R1 is an alkyl group having 4 or more carbon atoms.

[0034] Alcoholysis step (1) A process for preparing terephthalic acid according to one embodiment of the present invention includes subjecting waste polyester to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition comprising a compound represented by Formula 1.

[0035] Waste polyester can be obtained by crushing or melting waste polyester products. For example, waste polyester can be obtained by crushing or converting used, recovered and separated polyester products into pellets (post-consumer recycled material, PCR), or can be polyester waste such as rejects or scraps that can be formed during processes such as molding polyester films, fibers, containers, etc. (post-industrial recycled material, PIR).

[0036] Further, the number of carbon atoms of the alcohol may be 4 or more, 6 or more, 8 or more, 10 or more, or 12 or more, and may be 4-14, 4-13, 4-10, 4-8, 6-12, 8-14, or 8-13.

[0037] When the alcoholysis of waste polyester is carried out using an alcohol having the above number of carbon atoms, the alcoholysis can be carried out at a lower temperature and pressure than the conventional process using waste polyester, which is carried out at high temperature and high pressure, and the intermediate, i.e., the alcoholysis product, can be produced in liquid form. Furthermore, when the number of carbon atoms of the alcohol satisfies the above range, the reaction rate of the alcoholysis can be improved.

[0038] Further, the alcohol can have a boiling point of 100°C to 290°C. For example, the boiling point of the alcohol can be 100°C to 280°C, 100°C to 260°C, 100°C to 230°C, 110°C to 190°C, or 180°C to 290°C. When the boiling point of the alcohol satisfies the above range, the ethylene glycol formed as a by-product during alcoholysis can be more easily removed or recovered in the subsequent process, thereby further improving the processability. In particular, in the field in which polyester is used as a raw material, there has been a tendency to use various monomer materials in recent years, and therefore the removal of various dialcohol-type monomers used in waste polyester such as waste plastic products can be easily adopted.

[0039] The weight ratio of waste polyester to alcohol can be 1:1 to 10. For example, the weight ratio of waste polyester to alcohol can be 1:1 to 8, 1:1 to 6, 1:1 to 4, 1:1 to 3.5, 1:1.1 to 3.3, 1:2 to 4, or 1:2 to 3.5.

[0040] Further, the alcoholysis reaction can be carried out at a temperature of 160° C. to 280° C. and a pressure of 1 bar to 40 bar for 0.5 hours to 24 hours. For example, the alcoholysis reaction can be carried out at a temperature of 165° C. to 280° C., 165° C. to 270° C., 180° C. to 270° C., 190° C. to 250° C., 200° C. to 265° C., 220° C. to 265° C., 240° C. to 260° C., or 245° C. to 260° C., and at a pressure of 1 bar to 38 bar, 1 bar to 33 bar, 1 bar to 28 bar, 1 bar to 24 bar, 2 bar to 40 bar, 3 bar to 35 bar, or 5 bar to 30 bar for 0.5 hours to 22 hours, 1 hour to 15 hours, 1.5 hours to 10 hours, 2 hours to 8 hours, or 2 hours to 6 hours.

[0041] In step (1), an alcoholysis catalyst can be added. In particular, the alcoholysis reaction can be smoothly carried out as a non-catalyzed reaction without using an alcoholysis catalyst, which is environmentally friendly. In particular, when the content of insoluble metals in the waste polyester is high, the non-catalyzed reaction can be advantageous in terms of efficient processing and impurity removal. Furthermore, an alcoholysis catalyst can be added in step (1) from the viewpoint of energy in order to improve the processability by improving the reactivity.

[0042] The alcoholysis catalyst may be a metal acetate, an alkali metal salt or a hydroxy salt.

[0043] In particular, the alcoholysis catalyst is Li + , Na + , K + and Cs + Alkali metal ions such as Be 2+ , Mg 2+ , Ca 2+ and Ba 2+Alkaline earth metal ions such as NH 4+ and N.R. 4+ (wherein R is alkyl) and ammonium ions such as Zn 2+ At least one cation selected from the group consisting of - , OR - (where R is alkyl), HCO3 - , CO3 2- , benzoate ion (C7H5O2 - ), 4-alkoxycarbonylbenzoate ion, acetate ion, and terephthalate ion. R may be an alkyl group having 1 to 10 carbon atoms or an alkyl group having 1 to 5 carbon atoms.

[0044] For example, the alcoholysis catalyst may comprise at least one selected from the group consisting of Zn(OAC)2, Co(OAc)2, Mn(OAc)2, Mg(OAc)2, Ca(OAc)2, Ba(OAc)2, LiOAc, NaOAc, KOAc, Zn(OAC)2·2H2O, Co(OAc)2·4H2O, Pb(OAc)2, Mn(OAc)2·4H2O, Mg(OAc)2·4H2O, Pd(OAc)2, Ti(OBu)4, Ti(OiPr)4, GeO2, Al(OiPr)3, Na2CO3, K2CO3, dibutyltin(IV) oxide, stannous octoate, titanium phosphate, and terephthalic acid.

[0045] Further, the amount of the alcoholysis catalyst added can be 10 ppm to 10,000 ppm based on the total weight of the waste polyester. For example, the amount of the alcoholysis catalyst added can be 10 ppm to 9,000 ppm, 15 ppm to 8,000 ppm, 20 ppm to 6,000 ppm, 50 ppm to 3,500 ppm, 100 ppm to 1,500 ppm, 150 ppm to 1,000 ppm, 180 ppm to 500 ppm, or 200 ppm to 450 ppm based on the total weight of the waste polyester.

[0046] According to one embodiment of the present invention, a liquid composition comprising a compound represented by formula 1 is prepared by alcoholysis. In particular, the composition is liquid at room temperature, and the liquid composition is a composition produced by an alcoholysis reaction.

[0047] The liquid composition comprises a compound represented by Formula 1. [ka]

[0048] In formula 1, R1 is an alkyl group having 4 or more carbon atoms.

[0049] In particular, R1 may be butyl, n-butyl, isobutyl, tert-butyl, sec-butyl, 1-methyl-butyl, 1-ethyl-butyl, pentyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl, n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3-dimethylbutyl, 2-ethylbutyl, hexyl, 1-methylhexyl, 2-ethyl-1-hexyl, heptyl, n-heptyl, 1-methylheptyl, octyl, n-octyl, isooctyl, tert-octyl, 2-propylpentyl, n-nonyl, 2,2-dimethylheptyl, 1-ethyl-propyl, 1,1-dimethyl-propyl, isohexyl, 2-methylpentyl, 4-methylhexyl, 5-methylhexyl, decanyl, undecanyl, dodecanyl, tridecanyl or tetradecanyl.

[0050] In particular, the liquid composition may include unreacted alcohol and ethylene glycol (EG) as a by-product. In particular, the liquid composition may include the compound represented by Formula 1, ethylene glycol (EG) formed as a by-product from the alcoholysis reaction, unreacted alcohol, and oligomers.

[0051] For example, the liquid composition can include a compound represented by Formula 2, and the oligomer can include a compound represented by Formula 3. [ka]

[0052] In formulas 2 and 3, R1 is an alkyl group having 4 or more carbon atoms, and n is an integer of 1 or more.

[0053] According to one embodiment of the present invention, the liquid composition may contain unreacted alcohol and ethylene glycol as a by-product, and the content of the compound represented by formula 1 in the liquid composition may be 70 mol% or more. For example, the content of the compound represented by formula 1 in the liquid composition prepared by alcoholysis may be 72 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 91 mol% or more, 92 mol% or more, 92.5 mol% or more, 93 mol% or more, 95 mol% or more, 97 mol% or more, 99 mol% or more, or 99.5 mol% or more.

[0054] Further, the content of the oligomer in the liquid composition may be 15 mol% or less. For example, the content of the oligomer in the liquid composition may be 11 mol% or less, 8.5 mol% or less, 7 mol% or less, 5 mol% or less, 3 mol% or less, 1 mol% or less, 0.8 mol% or less, 0.4 mol% or less, or 0.1 mol% or less.

[0055] According to another embodiment of the present invention, step (1) may include draining off unreacted alcohol and ethylene glycol as a by-product.

[0056] In particular, alcohol is separated from the discharged mixture of alcohol and ethylene glycol, and the separated alcohol can be reused as a raw material for alcoholysis. For example, ethylene glycol as a by-product formed in the alcoholysis and unreacted alcohol (alcohol present in excess) can be discharged in the form of a gas mixture immediately during the alcoholysis reaction and fractionated or phase-separated, and / or fractionated after completion of the reaction to separate the alcohol and ethylene glycol. The separated alcohol can be reintroduced into the alcoholysis in step (1) for reuse. In such a case, the volume and feed rate of the alcohol introduced for reuse can be the same as the volume and discharge rate of the discharged mixture of alcohol and ethylene glycol.

[0057] Additionally, step (1) may include recovering ethylene glycol as a by-product of the alcoholysis. In particular, the ethylene glycol as a by-product of the alcoholysis may be recovered by fractional distillation or phase separation of the discharged mixture of alcohol and ethylene glycol, or by fractional distillation or phase separation of the composition prepared in step (1).

[0058] For example, unreacted alcohol and ethylene glycol as a by-product are immediately discharged during the alcoholysis reaction as a gas mixture, which is condensed using an external cooling device to recover the ethylene glycol.

[0059] According to one embodiment of the present invention, the unreacted alcohol and ethylene glycol can be separated by a simple process such as fractional distillation or phase separation, and the separated unreacted alcohol can be reused as a raw material for alcoholysis, and the recovered ethylene glycol can be used in another process, thus providing excellent processability and reducing process costs.

[0060] The recovery rate of ethylene glycol can be 65% or greater. For example, the recovery rate of ethylene glycol can be 70% or greater, 76% or greater, 85% or greater, 90% or greater, 93% or greater, 95% or greater, 97% or greater, 98% or greater, 99% or greater, or 99.5% or greater.

[0061] Purification Step The process for preparing terephthalic acid according to another embodiment of the present invention may further comprise purifying the liquid composition prior to step (2).

[0062] In particular, the purification step may include the addition of at least one adsorbent selected from the group consisting of activated carbon, silica gel, alumina, zeolite and activated clay or adsorption through bed adsorption. In particular, the adsorbent may be activated carbon or a mixture of activated carbon and silica gel. For example, the adsorbent may be, but is not limited to, a mixture of activated carbon and silica gel in a weight ratio of 1:0.5-1.5 or 1:0.8-1.2.

[0063] The content of the adsorbent added may be 0.1% to 20% by weight based on the total weight of the liquid composition. For example, the content of the adsorbent added may be 0.1% to 18% by weight, 0.1% to 15% by weight, 0.1% to 10% by weight, 0.1% to 5% by weight, or 0.1% to 2% by weight based on the total weight of the liquid composition.

[0064] When the step of purifying the liquid composition using an adsorbent, particularly using an adsorbent that meets the specific supply amount within the above numerical range, is further performed, the purity and yield can be further improved. In particular, when the step of purifying the liquid composition that is the alcoholysis reaction composition is performed, it is possible to more efficiently remove insoluble impurities such as metals that may be contained in the alcoholysis reaction composition or additives such as colorants and pigments that may be contained in the waste polyester. Therefore, the purity and yield of the finally prepared terephthalic acid can be further improved.

[0065] Furthermore, the process for preparing terephthalic acid according to another embodiment of the present invention may further include a concentration step after the purification step.

[0066] This concentration can be carried out for 0.5 to 6 hours at a temperature of 50° C. to 120° C. For example, the concentration can be carried out by stirring the purified alcoholysis reaction composition at a temperature of 55° C. to 115° C., 60° C. to 110° C., 65° C. to 105° C., or 75° C. to 100° C. for 1 to 5 hours, 1.5 to 4 hours, or 2 to 4 hours.

[0067] According to one embodiment of the present invention, the purified composition may have a % pigment retention of 15% or less according to Formula A. For example, the % pigment retention of the purified alcoholysis reaction composition according to Formula A may be 13% or less, 11% or less, 10% or less, 8% or less, 6% or less, 5.5% or less, 5% or less, 4.3% or less, or 4% or less.

number

[0068] In formula A, A1 is the area of ​​the absorbance curve obtained at 400 nm to 800 nm using a UV-vis spectrophotometer for a purified alcoholysis reaction composition diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) or methylpyrrolidone (NMP), and A2 is the area of ​​the absorbance curve obtained in the same manner as above for an unpurified alcoholysis reaction composition.

[0069] The explanation regarding purification in formula A is as described above.

[0070] The pigment residual ratio means the content of additives such as colorants, pigments, dyes, etc. remaining in the composition. The lower the pigment residual ratio, the lower the content of additives such as colorants, pigments, dyes, etc., and the higher the purity.

[0071] Additionally, the purified composition may have a reduced content of insoluble impurities such as metals. In particular, the purified liquid composition may have a total metal content of 100 ppm or less based on the total weight of the purified alcoholysis reaction composition, as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0072] For example, the purified alcoholysis reaction composition may contain insoluble impurities such as metals. The total content of metals in the purified alcoholysis reaction composition may be 80 ppm or less, 70 ppm or less, 60 ppm or less, 50 ppm or less, 40 ppm or less, or less than 30 ppm based on the total weight of the purified alcoholysis reaction composition, as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). In particular, the total content of Sb, Ti, and Zn in the purified alcoholysis reaction composition may be less than 30 ppm, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less.

[0073] Sb is known to be a widely used catalyst in the polymerization of common polyesters due to its excellent stability, reaction rate and cost. However, due to the increasing regulation of Sb due to its effects on human health and the environment, it is a substance that needs to be removed during the chemical regeneration process.

[0074] In addition, Ti can be used as a catalyst for polyester polymerization or an additive for polyester processing in the form of TiO2. If it is contained in an amount greater than a certain amount, the quality of the recycled terephthalic acid prepared therefrom or the polyester resin using it may be reduced, thereby limiting its use.

[0075] Zn is also a component used as a polymerization catalyst for polyesters such as PET. If it remains, it may affect the control of reactivity in the preparation process of recycled terephthalic acid or polyester resin using it. Therefore, it is preferable to remove it. In particular, since it is widely used in chemical recycling processes, it is a substance that needs to be sufficiently removed in the amount contained in the waste plastics that are the raw material of this process and in the amount added separately as a catalyst during the recycling process.

[0076] According to one embodiment of the present invention, when further purification is carried out, the total content of metals in the purified alcoholysis reaction composition, especially the aforementioned Sb, Ti and Zn, is very low, below 30 ppm.

[0077] For example, the Sb content, as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), may be 30 ppm or less, 20 ppm or less, 10 ppm or less, or 1 ppm or less based on the total weight of the purified alcoholysis reaction composition.

[0078] When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Ti content may be 30 ppm or less, 20 ppm or less, 10 ppm or less, or 1 ppm or less based on the total weight of the purified alcoholysis reaction composition.

[0079] The Zn content, as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), may be 30 ppm or less, 20 ppm or less, 10 ppm or less, or 1 ppm or less based on the total weight of the purified alcoholysis reaction composition.

[0080] Hydrolysis reaction step (2) The process for preparing terephthalic acid according to one embodiment of the present invention includes subjecting a composition to hydrolysis. In particular, in step (2), the alcoholysis reaction composition (a liquid composition containing a compound represented by formula I) prepared in step (1) or the purified alcoholysis reaction composition can be subjected to hydrolysis to prepare regenerated terephthalic acid.

[0081] The hydrolysis can be carried out by adding water to the composition. For example, the hydrolysis can be carried out by adding water to the alcoholysis reaction composition or the purified alcoholysis reaction composition at a temperature of 180°C to 280°C, 185°C to 280°C, 200°C to 275°C, 220°C to 270°C, or 240°C to 265°C for 0.5 to 24 hours, 1 to 20 hours, 2.5 to 12 hours, or 3 to 8 hours.

[0082] The conventional method in which metal catalyst such as iron, cobalt, manganese or nickel is added to waste polyester and then directly hydrolyzed with water is environmentally friendly. However, it requires very high temperature conditions of 300°C or more, and the reactor also needs to be resistant to high pressure, which results in poor processability. In contrast, the process of preparing terephthalic acid according to one embodiment of the present invention has better processability because the process conditions are improved compared to the conventional technology.

[0083] Further, the weight ratio of the composition to water may be 1:1 to 500. For example, the weight ratio of the alcoholysis reaction composition (purified or purified and concentrated alcoholysis reaction composition) used during hydrolysis to water may be 1:1 to 450, 1:1 to 400, 1:1 to 250, 1:1 to 100, 1:1 to 50, 1:1.2 to 20, or 1:1.5 to 10.

[0084] Additionally, in step (2), a hydrolysis catalyst can be added, particularly to the mixture of the alcoholysis reaction composition and water to carry out the hydrolysis.

[0085] The hydrolysis reaction can be smoothly carried out as a non-catalyzed reaction without using a hydrolysis catalyst, and therefore is environmentally friendly. Especially when the content of insoluble metals in the waste polyester is high, the non-catalyzed reaction can be advantageous in terms of efficient processing and impurity removal. Furthermore, a hydrolysis catalyst can be added in step (2) to improve the processability by improving the reactivity from an energy perspective.

[0086] The hydrolysis catalyst may be a metal acetate, an alkali metal salt or a hydroxy salt.

[0087] In particular, the hydrolysis catalyst is Li + , Na + , K + and Cs + Alkali metal ions such as Be 2+ , Mg 2+ , Ca 2+ and Ba 2+ Alkaline earth metal ions such as NH 4+ and N.R. 4+ (wherein R is alkyl) and ammonium ions such as Zn 2+ At least one cation selected from the group consisting of - , OR - (where R is alkyl), HCO3 - , CO3 2- , benzoate ion (C7H5O2 - ), 4-alkoxycarbonylbenzoate ion, acetate ion, and terephthalate ion. R may be an alkyl group having 1 to 10 carbon atoms or an alkyl group having 1 to 5 carbon atoms.

[0088] For example, the hydrolysis catalyst may include at least one selected from the group consisting of Zn(OAC)2, Co(OAc)2, Mn(OAc)2, Mg(OAc)2, Ca(OAc)2, Ba(OAc)2, LiOAc, NaOAc, KOAc, Zn(OAC)2·2H2O, Co(OAc)2·4H2O, Pb(OAc)2, Mn(OAc)2·4H2O, Mg(OAc)2·4H2O, Pd(OAc)2, Ti(OBu)4, Ti(OiPr)4, GeO2, Al(OiPr)3, Na2CO3, K2CO3, dibutyltin(IV) oxide, stannous octoate, titanium phosphate, and terephthalic acid.

[0089] Further, the amount of hydrolysis catalyst added may be 10 ppm to 10,000 ppm based on the total weight of the composition. For example, the amount of hydrolysis catalyst added may be 15 ppm to 8,000 ppm, 20 ppm to 5,500 ppm, 30 ppm to 3,000 ppm, 50 ppm to 1,600 ppm, 100 ppm to 1,200 ppm, 150 ppm to 1,100 ppm, 300 ppm to 1,000 ppm, 350 ppm to 950 ppm, 400 ppm to 850 ppm, 420 ppm to 700 ppm, or 450 ppm to 650 ppm based on the total weight of the alcoholysis reaction composition (purified or purified and concentrated alcoholysis reaction composition).

[0090] According to one embodiment of the present invention, solid terephthalic acid can be prepared by hydrolysis.In particular, this process can further include filtering, washing and drying the hydrolysis reaction product prepared by hydrolysis after the hydrolysis step.That is, the hydrolysis reaction product prepared by hydrolysis can be filtered, washed and dried to produce solid terephthalic acid.

[0091] For example, the hydrolysis reaction product may be cooled to a suitable temperature, for example, room temperature to less than 100° C., at which temperature water does not evaporate, resulting in a solution in the form of a slurry, which is filtered to obtain a solid, which is washed and dried under reduced pressure to obtain solid terephthalic acid.

[0092] Washing can be carried out with a mixture of alcohols having 4 or more carbon atoms and / or water, protic solvents such as isopropanol and acetic acid, or aprotic solvents such as acetone, dichloromethane, chloroform, tetrahydrofuran (THF) and toluene.

[0093] Here, the description regarding the alcohol having 4 or more carbon atoms is as described above. The alcohol having 4 or more carbon atoms used for washing may be the same as or different from the alcohol having 4 or more carbon atoms used in step (1). For example, when 1-butanol is used as the alcohol in step (1) for producing terephthalic acid, the prepared solid terephthalic acid may be washed with a mixture of 1-butanol and water. Furthermore, the number of carbon atoms in the alcohol used for washing may be the same as the number of carbon atoms in the alcohol used in step (1).

[0094] The residual pigment or impurities generated by decomposition of the pigment during hydrolysis, especially the yellow impurities, can be effectively removed by washing, thereby improving the yellowness index or color properties. Furthermore, if water is used for washing, inorganic salts can be removed, thereby improving the quality.

[0095] Furthermore, the yield of terephthalic acid may be 65% or more. For example, the yield of the finally produced recycled terephthalic acid may be 68% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more.

[0096] Regenerated terephthalic acid Regenerated terephthalic acid according to another embodiment of the present invention is prepared by the process for preparing terephthalic acid described above and has a total metal content of less than 100 ppm as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0097] In particular, recycled terephthalic acid can be prepared by a process for preparing terephthalic acid.

[0098] The recycled terephthalic acid can have a total metals content of less than 100 ppm, 90 ppm or less, 80 ppm or less, 65 ppm or less, 50 ppm or less, 35 ppm or less, less than 30 ppm, 15 ppm or less, 9 ppm or less, 7 ppm or less, 5 ppm or less, or 1 ppm or less, as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0099] Furthermore, the recycled terephthalic acid can have a total content of Sb, Ti and Zn of less than 30 ppm as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES). For example, the total content of Sb, Ti and Zn in the recycled terephthalic acid, which may be harmful to the human body or may function as a catalyst for a reaction or side reaction in a subsequent polymerization process, can be 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less.

[0100] For example, when measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Sb content in the recycled terephthalic acid can be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less, based on the total weight of the recycled terephthalic acid.

[0101] When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Ti content in the recycled terephthalic acid may be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less, based on the total weight of the recycled terephthalic acid.

[0102] When measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), the Zn content in the recycled terephthalic acid may be 30 ppm or less, 25 ppm or less, 20 ppm or less, 15 ppm or less, 10 ppm or less, 5 ppm or less, 3 ppm or less, or 1 ppm or less, based on the total weight of the recycled terephthalic acid.

[0103] The recycled terephthalic acid can have a color-b, as measured using a colorimeter, of less than 2, 1.6 or less, 1.4 or less, 1.3 or less, or 1 or less. The above numerical range of color-b is equivalent to that of virgin terephthalic acid generally produced in a petrochemical process, so that recycled terephthalic acid satisfying the above range of color-b not only has a low yellowness index, but also has excellent quality because the monomer is sufficiently refined.

[0104] Col-b is a color coordinate established by the International Commission on Illumination (CIE) where color is expressed by L (lightness), a (complementary color from green to red) and b (complementary color from yellow to blue). It can be measured using a colorimeter.

[0105] Additionally, the recycled terephthalic acid may have a pigment residual rate of 10% or less according to formula B. For example, the pigment residual rate of the recycled terephthalic acid may be 10% or less, 8% or less, 7% or less, 5% or less, or 4% or less.

number

[0106] In formula B, B1 is the area of ​​the absorbance curve obtained from 400 nm to 800 nm using a UV-vis spectrophotometer for regenerated terephthalic acid diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) or methylpyrrolidone (NMP), and B2 is the area of ​​the absorbance curve obtained in the same manner as above for regenerated terephthalic acid that is not purified during its preparation process.

[0107] B1 can be measured for recycled terephthalic acid produced by carrying out a purification step or a purification and concentration step in the process of preparing recycled terephthalic acid. B2 can be measured for recycled terephthalic acid produced without a purification step or produced by carrying out only a concentration step in the process of preparing recycled terephthalic acid.

[0108] Furthermore, when the recycled terephthalic acid is diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and methylpyrrolidone (NMP), the yellowness index (YI) may be less than 2, 1.8 or less, or 1.7 or less, when measured. The yellowness index may be measured for recycled terephthalic acid produced by carrying out a purification step or a purification and concentration step in the process of preparing recycled terephthalic acid.

[0109] Polyester resin and its preparation process A polyester resin according to another embodiment of the invention includes recycled terephthalic acid.

[0110] In particular, the polyester resin may include recycled terephthalic acid, a diol compound or a derivative thereof, and optionally a dicarboxylic acid compound or a derivative thereof.

[0111] For example, the diol component or its derivative may include at least one selected from the group consisting of ethylene glycol, monoethylene glycol, diethylene glycol, 1,4-butanediol, 1,3-propanediol, 1,4-cyclohexanedimethanol, and neopentyl glycol. The dicarboxylic acid or its derivative may include at least one selected from the group consisting of terephthalic acid (TPA), isophthalic acid (IPA), 2,6-naphthalenedicarboxylic acid (2,6-NDA), dimethyl terephthalate (DMT), dimethyl isophthalate (DMI), and dimethyl 2,6-naphthalenedicarboxylate (2,6-NDC). However, it is not limited thereto.

[0112] A process for preparing a polyester resin according to another embodiment of the present invention includes mixing recycled terephthalic acid with a diol compound or a derivative thereof and optionally a dicarboxylic acid compound or a derivative thereof, and then carrying out an esterification reaction, and subjecting the esterification reaction product to a polycondensation reaction.

[0113] The esterification reaction can be carried out at a temperature of 200° C. to 350° C., 220° C. to 320° C., or 250° C. to 290° C. Furthermore, the esterification reaction can be carried out at a pressure of 0 kg / cm below standard pressure. 2 ~10kg / cm 2 (0mmHg~7,355.6mmHg), 0kg / cm 2 ~5kg / cm 2 (0-3,677.8mmHg) or 0kg / cm 2 ~2.0kg / cm 2 The esterification reaction can be carried out under a high pressure condition (0 to 1,471.1 mmHg). Furthermore, the esterification reaction can be carried out for 1 hour to 24 hours, 1 hour to 10 hours, or 1 hour to 6 hours.

[0114] Furthermore, the polycondensation reaction can be carried out at a temperature of 150°C to 400°C, 200°C to 370°C, 250°C to 350°C, or 270°C to 300°C. Furthermore, the polycondensation reaction can be carried out at a reduced pressure of 0.01mmHg to 400mmHg, 0.05mmHg to 100mmHg, or 0.1mmHg to 100mmHg. Furthermore, the polycondensation reaction can be carried out for a required time until the desired intrinsic viscosity is reached. For example, this can be carried out for 1 hour to 24 hours, 1 hour to 10 hours, or 1 hour to 4 hours.

[0115] Furthermore, catalysts and / or stabilizers may be further added to the esterification and polycondensation reactions.

[0116] For example, catalysts for the esterification reaction can be sodium and magnesium methylates, acetates, borates, fatty acid salts and carbonates of Zn, Cd, Mn, Co, Ca and Ba, metallic Mg and oxides of Pb, Zn, Sb and Ge.

[0117] Further, the catalyst for the polycondensation reaction may be, for example, a titanium-based catalyst, such as tetraethyl titanate, acetyl tripropyl titanate, tetrapropyl titanate, tetrabutyl titanate, polybutyl titanate, 2-ethylhexyl titanate, octylene glycol titanate, lactate titanate, triethanolamine titanate, acetylacetonate titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, titanium dioxide / silicon dioxide copolymer, titanium dioxide / zirconium dioxide copolymer, germanium-based catalyst, such as germanium dioxide and copolymers therewith, or a tin-based catalyst, such as monobutyltin oxide, dibutyltin oxide, and monobutylhydroxytin oxide.

[0118] Additionally, the stabilizer may be a phosphorus-based compound, such as, but not limited to, phosphoric acid, trimethyl phosphate, and triethyl phosphate.

[0119] The preparation process of the polyester resin according to another embodiment of the present invention may further include carrying out a solid-state polymerization reaction. For example, the solid-state polymerization may be carried out after a polycondensation reaction at a temperature of 190°C to 230°C under a vacuum condition of 0.2 torr to 2.0 torr or under a nitrogen atmosphere.

[0120] Aspects of the invention Hereinafter, the present invention will be described in more detail with reference to the following examples. However, these examples are provided to illustrate the present invention, and the scope of the present invention is not limited thereto. EXAMPLES

[0121] Preparation of Liquid Compositions Example 1-1 A first high-pressure reactor with a volume of 7 L was charged with 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as alcohol, followed by the addition of 200 mg of Zn(OAC)2·2H2O (200 ppm relative to the total weight of waste PET) as an alcoholysis catalyst.

[0122] Then, all connections of the first high-pressure reactor were tightened and sealed, the temperature was increased to 250° C. in 1 hour, and the alcoholysis reaction was carried out with stirring for 3 hours while maintaining the temperature at 250° C. and the pressure at 24 bar.

[0123] After the alcoholysis reaction was completed, the mixture was cooled to room temperature to obtain a liquid alcoholysis reaction composition, which was analyzed by NMR for its components and content. The alcoholysis reaction composition contained the compound represented by formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.

[0124] The alcoholysis reaction mixture was then charged into another flask, and a fractional distillation apparatus was used to recover the excess unreacted 1-butanol and the produced ethylene glycol (EG), respectively. [ka]

[0125] Example 1-2 A first high-pressure reactor with a volume of 7 L was charged with 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as alcohol, followed by the addition of 200 mg of Zn(OAC)2·2H2O (200 ppm relative to the total weight of waste PET) as an alcoholysis catalyst.

[0126] Then, all connections of the first high-pressure reactor were tightened and sealed, the temperature was increased to 250° C. in 1 hour, and the alcoholysis reaction was carried out with stirring for 3 hours while maintaining the temperature at 250° C. and the pressure at 24 bar.

[0127] In particular, one hour after the start of the alcoholysis reaction, the valve of the previously installed back pressure control device was adjusted to discharge a gas mixture of ethylene glycol (EG), a by-product produced by the alcoholysis reaction, and 1-butanol present in excess. In this case, the internal temperature of the first high-pressure reactor was maintained at 250°C, and the gas mixture of ethylene glycol (EG) and 1-butanol discharged from the back pressure control device was condensed using an external cooling device. Furthermore, the discharge rate of the gas mixture of ethylene glycol (EG) and 1-butanol was adjusted to 3 kg / h, and at the same time, 1-butanol was continuously supplied to the first high-pressure reactor. In this case, the volume and supply rate of 1-butanol newly supplied to the first high-pressure reactor were adjusted to be the same as the volume and discharge rate of the gas mixture of ethylene glycol (EG) and 1-butanol discharged. The alcoholysis reaction was carried out while maintaining the discharge and supply process for 3 hours.

[0128] After the alcoholysis reaction was completed, the mixture was cooled to room temperature to obtain a liquid alcoholysis reaction composition, which was analyzed by NMR for its components and content. The alcoholysis reaction composition contained the compound represented by formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.

[0129] The alcoholysis reaction mixture was then charged into another flask, and the excess unreacted 1-butanol and the produced ethylene glycol were each recovered using a fractional distillation apparatus. [ka]

[0130] Examples 1-3 A first high-pressure reactor with a volume of 7 L was charged with 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-butanol as alcohol, followed by the addition of 200 mg of Zn(OAC)2·2H2O (200 ppm relative to the total weight of waste PET) as an alcoholysis catalyst.

[0131] Then, all connections of the first high-pressure reactor were tightened and sealed, the temperature was increased to 250° C. in 1 hour, and the alcoholysis reaction was carried out with stirring for 3 hours while maintaining the temperature at 250° C. and the pressure at 24 bar.

[0132] Specifically, one hour after the start of the alcoholysis reaction, the valve of the previously installed back pressure control device was adjusted to discharge a gas mixture of ethylene glycol (EG), a by-product produced by the alcoholysis reaction, and 1-butanol present in excess. In this case, the internal temperature of the first high-pressure reactor was maintained at 250°C, and the gas mixture of ethylene glycol (EG) and 1-butanol discharged from the back pressure control device was condensed using an external cooling device. Furthermore, the discharge rate of the gas mixture of ethylene glycol (EG) and 1-butanol was adjusted to 3 kg / h, and at the same time, 1-butanol was continuously supplied to the first high-pressure reactor. In this case, the volume and supply rate of 1-butanol newly supplied to the first high-pressure reactor were adjusted to be the same as the volume and discharge rate of the gas mixture of ethylene glycol (EG) and 1-butanol discharged.

[0133] The condensed gas mixture of ethylene glycol (EG) and 1-butanol was transferred to a layer separation apparatus having a capacity of 5 liters and filled with 3 kg of water, and the procedure of stirring for 10 minutes and layer separation for 2 minutes was repeated to separate the 1-butanol layer and the water and ethylene glycol (EG) layer. The separated 1-butanol was immediately fed again to the first high-pressure reactor using the high-pressure pump. The alcoholysis reaction was carried out while maintaining the procedure of stirring, layer separation and reintroduction for 3 hours.

[0134] After the alcoholysis reaction was completed, the mixture was cooled to room temperature to obtain a liquid alcoholysis reaction composition, which was analyzed by NMR for its components and content. The alcoholysis reaction composition contained the compound represented by formula 1 (R1: (CH2)3CH3), residual ethylene glycol (EG), alcohol (1-butanol), and oligomers.

[0135] The alcoholysis reaction mixture was then charged into another flask, and the excess unreacted 1-butanol and the produced ethylene glycol were each recovered using a fractional distillation apparatus. [ka]

[0136] Examples 1-4 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.

[0137] Examples 1-5 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.

[0138] Examples 1-6 A liquid alcoholysis reaction composition was prepared similar to Examples 1-3, except that 3.3 kg of 1-pentanol was used as the alcohol and the pressure was maintained at 13 bar.

[0139] Examples 1-7 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.

[0140] Examples 1-8 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.

[0141] Examples 1-9 A liquid alcoholysis reaction composition was prepared similar to Examples 1-3, except that 3.3 kg of 1-octanol was used as the alcohol and the pressure was maintained at 3.4 bar.

[0142] Examples 1-10 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.

[0143] Examples 1-11 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.

[0144] Examples 1-12 A liquid alcoholysis reaction composition was prepared similar to Examples 1-3, except that 3.3 kg of 2-ethyl-1-hexanol was used as the alcohol and the pressure was maintained at 4.1 bar.

[0145] Examples 1-13 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 1-decanol was used as the alcohol and the pressure was maintained at 1.6 bar.

[0146] Examples 1-14 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of 1-decanol was used as the alcohol and the pressure was maintained at 1.6 bar.

[0147] Examples 1-15 A liquid alcoholysis reaction composition was prepared similar to Examples 1-3, except that 3.3 kg of 1-decanol was used as the alcohol and the pressure was maintained at 1.6 bar.

[0148] Examples 1-16 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 1-dodecanol was used as the alcohol and the pressure was maintained at 1.0 bar.

[0149] Examples 1-17 A first high-pressure reactor with a volume of 7 L was charged with 1 kg of waste polyethylene terephthalate (waste PET) and 3.3 kg of 1-dodecanol as alcohol, followed by the addition of 200 mg of Zn(OAC)2·2H2O (200 ppm relative to the total weight of waste PET) as an alcoholysis catalyst.

[0150] Then, all connections of the first high-pressure reactor were tightened and sealed, the temperature was increased to 250° C. in 1 hour, and the alcoholysis reaction was carried out with stirring for 3 hours while maintaining the temperature at 250° C. and the pressure at 1.0 bar.

[0151] In particular, one hour after the start of the alcoholysis reaction, the valve of the pre-installed back pressure control device was adjusted to discharge the vapor of ethylene glycol (EG), a by-product produced by the alcoholysis reaction. In this case, the internal temperature of the first high-pressure reactor was maintained at 250°C, and the vapor of ethylene glycol (EG) was condensed using an external cooling device.

[0152] Furthermore, 1-dodecanol was continuously fed to the first high-pressure reactor in an amount equal to the amount of ethylene glycol (EG) discharged as vapor and condensed. In this case, the volume and feed rate of 1-dodecanol newly fed to the first high-pressure reactor were adjusted to be the same as the volume and discharge rate of the ethylene glycol (EG) vapor discharged. The alcoholysis reaction was carried out while maintaining the discharge and feed process for 3 hours.

[0153] After the alcoholysis reaction was completed, it was cooled to room temperature to obtain a liquid alcoholysis reaction composition. Here, the components and contents of the alcoholysis reaction composition were analyzed by NMR. The alcoholysis reaction composition was a compound represented by formula 1 (R1: (CH2) 11 CH3), residual ethylene glycol (EG), alcohol (1-dodecanol) and oligomers.

[0154] The alcoholysis reaction mixture was then charged into another flask, and the excess unreacted 1-dodecanol and the produced ethylene glycol (EG) were each recovered using a fractional distillation apparatus. [ka]

[0155] Examples 1-18 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of 1-tetradecanol was used as the alcohol and the pressure was maintained at 1.0 bar.

[0156] Examples 1-19 A liquid alcoholysis reaction composition was prepared similarly to Examples 1-17, except that 3.3 kg of 1-tetradecanol was used as the alcohol.

[0157] Comparative Example 1-1 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of methanol was used as the alcohol and the pressure was maintained at 83 bar.

[0158] Comparative Example 1-2 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of methanol was used as the alcohol and the pressure was maintained at 83 bar.

[0159] Comparative Example 1-3 A liquid alcoholysis reaction composition was prepared similar to Example 1-1, except that 3.3 kg of ethanol was used as the alcohol and the pressure was maintained at 64 bar.

[0160] Comparative Example 1-4 A liquid alcoholysis reaction composition was prepared similar to Example 1-2, except that 3.3 kg of ethanol was used as the alcohol and the pressure was maintained at 64 bar.

[0161] [Table 1]

[0162] As can be seen from Table 1 above, when the liquid alcoholysis reaction compositions of Examples 1-1 to 1-19 were prepared using alcohols having 4 or more carbon atoms, they could be prepared at a much lower process pressure than those of Comparative Examples 1-1 to 1-4. The content of the compound represented by Formula 1, i.e., the yield and purity, were high, and the recovery rate of ethylene glycol was also excellent.

[0163] Purification and concentration of liquid compositions Example 2-1 Using the fractionating apparatus in Example 1-1, 0.1 g of activated carbon was added as an adsorbent to 100 g of the liquid alcoholysis reaction composition before recovering the excess unreacted alcohol and the produced ethylene glycol, followed by purification. The alcoholysis reaction composition was stirred at 100°C for 3 hours and then filtered to concentrate the alcoholysis reaction composition.

[0164] Examples 2-2 to 2-23 and Comparative Examples 2-1 and 2-2 The liquid alcoholysis reaction compositions were purified and concentrated in the same manner as in Example 2-1, except that the liquid composition and process conditions were changed as shown in Table 2 below, where in Comparative Examples 2-1 and 2-2, the liquid precipitated in an undissolved state and was not purified.

[0165] Examples 2-24 to 2-26 Using the fractionating apparatus in each of Examples 1-1, 1-4, and 1-10, 100 g of the liquid alcoholysis reaction composition after recovering excess unreacted alcohol and produced ethylene glycol was added with 0.1 g of activated carbon as an adsorbent, followed by purification, which was stirred at 100° C. for 3 hours and then filtered to concentrate the alcoholysis reaction composition.

[0166] Comparative Examples 2-3 to 2-21 Using the fractionation apparatus in each of Examples 1-1 to 1-19, the liquid alcoholysis reaction composition before recovering the excess unreacted alcohol and the produced ethylene glycol was stirred at 100°C for 3 hours without adding an adsorbent, and then filtered to concentrate it.

[0167] Test Example 1-1: Pigment Residual Rate The pigment residual rate (%) was measured for each of the compositions of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21.

[0168] Specifically, the composition of Example 2-1 was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and methylpyrrolidone (NMP), and the area (A1) of the absorbance curve at 400 nm to 800 nm was determined using a UV-vis spectrophotometer. Furthermore, in the case of the composition of Comparative Example 2-3 (the composition of Example 1-1 was used in the same manner as the composition of Example 2-1 described above, but this composition was concentrated without purification by adding an adsorbent), the area (A2) of the absorbance curve at 400 nm to 800 nm was determined in the same manner as above. Using the area of ​​the measured absorbance curve, the pigment residual rate (%) was calculated according to the following formula A.

number

[0169] For each of the compositions of Examples 2-2 to 2-26 and Comparative Examples 2-1 to 2-21, the pigment residual rate (%) was measured in the same manner as described above.

[0170] Test Example 1-2: Yellowness Index The yellowness index (YI) was measured for each of the compositions of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21.

[0171] Specifically, each of the compositions of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and methylpyrrolidone (NMP), and the yellowness index was measured using a ColorFlex EZ (manufacturer: HunterLab) device.

[0172] Test Example 1-3: Metal Content The metal content (ppm) present in each of the compositions of Examples 2-1 to 2-26 and Comparative Examples 2-1 to 2-21 was measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). ND means that the content is less than 1 ppm, which is too low to be measured as a specific value.

[0173] [Table 2-1]

[0174] [Table 2-2]

[0175] [Table 2-3]

[0176] As can be seen from Table 2 above, the purified and concentrated alcoholysis reaction compositions of Examples 2-1 to 2-26 had very low pigment residual rates and very low contents of metals such as Sb, Ti and Zn.

[0177] Preparation of terephthalic acid Example 3-1 Into a second high-pressure reactor having a capacity of 600 ml, 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged, followed by the addition of 50 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0178] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. The hydrolysis reaction product in the form of a slurry was filtered to obtain a solid, which was washed with butanol and water at 90°C and dried under vacuum to obtain 53.7g (yield: 90%) of solid terephthalic acid (TPA).

[0179] Example 3-2 A second high-pressure reactor having a capacity of 600 ml was charged with 100 g (0.30 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-5 and 200 g (11.10 mol) of water, followed by the addition of 50 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0180] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. The hydrolysis reaction product in the form of a slurry was filtered to obtain a solid, which was washed with pentanol and water at 90°C and dried under vacuum to obtain 43.9g (yield: 81%) of solid terephthalic acid (TPA).

[0181] Example 3-3 A second high-pressure reactor having a capacity of 600 ml was charged with 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-11 and 1,000 g (55.50 mol) of water, followed by the addition of 50 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0182] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. The hydrolysis reaction product in the form of a slurry was filtered to obtain a solid, which was washed with 2-ethyl-1-hexanol and water at 90°C and dried under vacuum to obtain 38.0g (yield: 88%) of solid terephthalic acid (TPA).

[0183] Examples 3-4 35.4 g (yield: 82%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-3, except that 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-13 was used.

[0184] Examples 3-5 36.7 g (yield: 85%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-3, except that 100 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-14 was used.

[0185] Examples 3-6 A second high-pressure reactor having a capacity of 600 ml was charged with 114 g (0.26 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-18 and 200 g (11.10 mol) of water, followed by the addition of 57 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0186] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. The hydrolysis reaction product in the form of a slurry was filtered to obtain a solid, which was washed with decanol and water at 90°C and dried under vacuum to obtain 36.1g (yield: 85%) of solid terephthalic acid (TPA).

[0187] Examples 3-7 Solid terephthalic acid (TPA) (54.3 g, yield: 91%) was obtained in the same manner as in Example 3-1, except that no hydrolysis catalyst was added.

[0188] Examples 3-8 Into a second high-pressure reactor having a capacity of 600 ml, 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged, followed by the addition of 50 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0189] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. Acetone was added to the solid obtained by filtering the hydrolysis reaction product in the form of a slurry, followed by stirring at 50°C for 4 hours. It was filtered, then washed with acetone and water at 50°C, and dried under vacuum to obtain 55.6g (yield: 93%) of solid terephthalic acid (TPA).

[0190] Examples 3-9 Into a second high-pressure reactor having a capacity of 600 ml, 100 g (0.36 mol) of the purified and concentrated alcoholysis reaction composition of Example 2-2 and 200 g (11.10 mol) of water were charged, followed by the addition of 50 mg of Zn(OAC)2·2H2O (500 ppm based on the total weight of the purified and concentrated alcoholysis reaction composition).

[0191] Then, the temperature of the second high-pressure reactor was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, followed by cooling to 90°C to obtain a hydrolysis reaction product in the form of a slurry. Butanol was added to the solid obtained by filtering the hydrolysis reaction product in the form of a slurry, followed by stirring at 90°C for 4 hours. This was filtered, then washed with butanol and water at 50°C, and dried under vacuum to obtain 53.1g (yield: 89%) of solid terephthalic acid (TPA).

[0192] Examples 3-10 Solid terephthalic acid (TPA) of 59.2 g (yield: 99%) was obtained in the same manner as in Example 3-1, except that the filtrate separated by the filtration step in Example 3-1 was further used.

[0193] Specifically, the filtrate separated in the filtration step of Example 3-1 was again charged into the second high-pressure reactor, the temperature was increased to 260°C, and the hydrolysis reaction was carried out for 4 hours while maintaining the temperature at 260°C, and then cooled to 90°C to obtain a hydrolysis reaction product in the form of a slurry. The hydrolysis reaction product in the form of a slurry was filtered to obtain a solid, which was washed with butanol and water at 90°C and dried under vacuum to obtain 5.5g of solid terephthalic acid (TPA).

[0194] Comparative Example 3-1 Except for using 100 g (0.36 mol) of the composition of Comparative Example 2-4, 54.4 g (yield: 91%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-1.

[0195] Comparative Example 3-2 Except for using 100 g (0.30 mol) of the composition of Comparative Example 2-7, 40.4 g (yield: 81%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-2.

[0196] Comparative Example 3-3 Except for using 100 g (0.26 mol) of the composition of Comparative Example 2-13, 36.7 g (yield: 85%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-3.

[0197] Comparative Example 3-4 Except for using 114 g (0.26 mol) of the composition of Comparative Example 2-16, 34.4 g (yield: 81%) of solid terephthalic acid (TPA) was obtained in the same manner as in Example 3-6.

[0198] Test Example 2-1: Pigment Residual Rate The pigment residual rate (%) was measured for each of the terephthalic acids in Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4.

[0199] Specifically, the terephthalic acid of Example 3-1 was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and methylpyrrolidone (NMP), and the area (B1) of the absorbance curve at 400 nm to 800 nm was determined using a UV-vis spectrophotometer. Furthermore, in the case of the composition of Comparative Example 2-4 (the composition of Example 1-2 was used in the same manner as the composition of Example 1-2 used in the preparation of the terephthalic acid of Example 3-1, but this composition was concentrated without adding an adsorbent), the area (B2) of the absorbance curve at 400 nm to 800 nm was determined in the same manner as above. The pigment residual rate (%) was calculated using the measured area of ​​the absorbance curve according to the following formula B.

number

[0200] The pigment residual rate (%) was measured in the same manner as described above for each of the terephthalic acids in Examples 3-2 to 3-10 and Comparative Examples 3-1 to 3-4. In particular, with respect to B2 in the above formula 1, Example 3-2 was measured using the composition of Comparative Example 2-7, Examples 3-3 to 3-5 were measured using the composition of Comparative Example 2-13, and Example 3-6 was measured using the composition of Comparative Example 2-16. Furthermore, in Comparative Examples 3-1 to 3-4, B2 in formula 1 was measured using the compositions of Comparative Examples 2-4, 2-7, 2-13, and 2-16, respectively.

[0201] Test Example 2-2: Yellowness Index The yellowness index (YI) was measured for each of the recycled terephthalic acids of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4.

[0202] Specifically, the recycled terephthalic acid of each of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4 was diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and methylpyrrolidone (NMP), and the yellowness index was measured using a ColorFlex EZ (manufacturer: HunterLab) device.

[0203] Test Example 2-3: Metal Content The metal content (ppm) in each of the terephthalic acids of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-10 was measured using inductively coupled plasma atomic emission spectrometry (ICP-AES). ND means that the content is less than 1 ppm, which is too low to be measured as a specific value.

[0204] Test Example 2-4: Color-b For each of the terephthalic acids of Examples 3-1 to 3-10 and Comparative Examples 3-1 to 3-4, the color characteristic color-b was measured using a colorimeter.

[0205] [Table 3]

[0206] As can be seen from Table 3 above, the terephthalic acid (regenerated terephthalic acid) prepared in Examples 3-1 to 3-6 not only has low pigment retention and low yellowness index, but also has very low metal content as impurities. In particular, in Example 3-10, regenerated terephthalic acid was obtained in a very high yield using the filtrate, i.e., the unreacted material separated by the filtration step.

Claims

1. 1. A process for preparing terephthalic acid, comprising: (1) subjecting waste polyester to alcoholysis with an alcohol having 4 or more carbon atoms to prepare a liquid composition comprising a compound represented by formula 1; (2) subjecting the liquid composition to hydrolysis; 【Chemistry 1】 [In formula 1, R 1 is an alkyl group having 4 or more carbon atoms. The process includes:

2. 2. The process for preparing terephthalic acid according to claim 1, wherein the number of carbon atoms of the alcohol is 4 to 14.

3. 2. The process for preparing terephthalic acid according to claim 1, wherein the weight ratio of said waste polyester to said alcohol is 1:1-10.

4. 2. The process for preparing terephthalic acid according to claim 1, wherein the alcoholysis is carried out at a temperature of 160° C. to 280° C. and a pressure of 1 bar to 40 bar for a period of 0.5 hours to 24 hours.

5. 2. The process for preparing terephthalic acid according to claim 1, wherein the liquid composition comprises unreacted alcohol and ethylene glycol as a by-product, and the content of the compound represented by formula 1 in the liquid composition is 70 mol% or more.

6. 2. The process for preparing terephthalic acid according to claim 1, wherein step (1) comprises discharging the unreacted alcohol and ethylene glycol as a by-product, the alcohol being separated from the discharged mixture of alcohol and ethylene glycol, and the separated alcohol being reused as a raw material for the alcoholysis.

7. 2. The process for preparing terephthalic acid according to claim 1, wherein step (1) comprises recovering ethylene glycol as a by-product of the alcoholysis, and the recovery rate of ethylene glycol is 65% or more.

8. In step (1), an alcoholysis catalyst is added; The alcoholysis catalyst is Li + , Na + , K + and Cs + Alkali metal ions of Be 2+ , Mg 2+ , Ca 2+ and Ba 2+ Alkaline earth metal ions, NH 4+ and N.R. 4+ (wherein R is alkyl) and ammonium ions of Zn 2+ At least one cation selected from the group consisting of: - , OR - (wherein R is alkyl), HCO 3 - , CO 3 2- , benzoate ion (C 7 H 5 O 2 - ), at least one anion selected from the group consisting of 4-alkoxycarbonylbenzoate, acetate, and terephthalate; and 2. The process for preparing terephthalic acid according to claim 1, wherein the amount of the alcoholysis catalyst added is 10 ppm to 10,000 ppm based on the total weight of the waste polyester.

9. In step (1), an alcoholysis catalyst is added; The alcoholysis catalyst is Zn(OAC) 2 , Co(OAc) 2 , Mn(OAc) 2 , Mg(OAc) 2 , Ca(OAc) 2 , Ba(OAc) 2 , LiOAc, NaOAc, KOAc, Zn(OAC) 2 ・2H 2 O, Co(OAc) 2 ・4H 2 O, Pb(OAc) 2 , Mn(OAc) 2 ・4H 2 O, Mg(OAc) 2 ・4H 2 O, Pd(OAc) 2 , Ti(OBu) 4 , Ti(OiPr) 4 , GeO 2 , Al(OiPr) 3 , Na 2 CO 3 , K 2 CO 3 , dibutyltin (IV) oxide, stannous octoate, titanium phosphate, and terephthalic acid; and 2. The process for preparing terephthalic acid according to claim 1, wherein the amount of the alcoholysis catalyst added is 10 ppm to 10,000 ppm based on the total weight of the waste polyester.

10. 2. The process for preparing terephthalic acid according to claim 1, further comprising purifying the liquid composition prior to step (2).

11. The process of preparing terephthalic acid according to claim 10, wherein the purification step comprises adding at least one adsorbent selected from the group consisting of activated carbon, silica gel, alumina, zeolite and activated clay or adsorption through bed adsorption, and the content of the adsorbent added is 0.1 wt% to 20 wt% based on the total weight of the liquid composition.

12. 2. The process of preparing terephthalic acid as claimed in claim 1, wherein said hydrolysis is carried out by adding water to said liquid composition at a temperature of 180°C to 280°C for a period of 0.5 hours to 24 hours.

13. 12. The process for preparing terephthalic acid according to claim 11, wherein the weight ratio of the liquid composition to water is 1:1-500.

14. In step (2), a hydrolysis catalyst is added; The hydrolysis catalyst is Li + , Na + , K + and Cs + Alkali metal ions of Be 2+ , Mg 2+ , Ca 2+ and Ba 2+ Alkaline earth metal ions, NH 4+ and N.R. 4+ (wherein R is alkyl) and ammonium ions of Zn 2+ At least one cation selected from the group consisting of: - , OR - (wherein R is alkyl), HCO 3 - , CO 3 2- , benzoate ion (C 7 H 5 O 2 - ), at least one anion selected from the group consisting of 4-alkoxycarbonylbenzoate, acetate, and terephthalate; and 2. The process for preparing terephthalic acid according to claim 1, wherein the amount of the hydrolysis catalyst added is from 10 ppm to 10,000 ppm based on the total weight of the liquid composition.

15. The hydrolysis catalyst is Zn(OAC) 2 , Co(OAc) 2 , Mn(OAc) 2 , Mg(OAc) 2 , Ca(OAc) 2 , Ba(OAc) 2 , LiOAc, NaOAc, KOAc, Zn(OAC) 2 ・2H 2 O, Co(OAc) 2 ・4H 2 O, Pb(OAc) 2 , Mn(OAc) 2 ・4H 2 O, Mg(OAc) 2 ・4H 2 O, Pd(OAc) 2 , Ti(OBu) 4 , Ti(OiPr) 4 , GeO 2 , Al(OiPr) 3 , Na 2 CO 3 , K 2 CO 3 , dibutyltin (IV) oxide, stannous octoate, titanium phosphate, and terephthalic acid; and 2. The process for preparing terephthalic acid according to claim 1, wherein the amount of the hydrolysis catalyst added is from 10 ppm to 10,000 ppm based on the total weight of the liquid composition.

16. 13. Regenerated terephthalic acid prepared by the process for preparing terephthalic acid of claim 1 and having a total metal content of less than 100 ppm as measured by inductively coupled plasma atomic emission spectrometry (ICP-AES).

17. 17. The regenerated terephthalic acid of claim 16, having a total Sb, Ti and Zn content of less than 30 ppm as measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES).

18. 17. The regenerated terephthalic acid according to claim 16, wherein the regenerated terephthalic acid has a yellowness index (Y.I.) of less than 2 when diluted to a concentration of 5% in dimethyl sulfoxide (DMSO), dimethylformamide (DMF) or methylpyrrolidone (NMP), respectively, and measured.

19. A polyester resin comprising the recycled terephthalic acid of claim 16.

Citation Information

Patent Citations

  • Device and process for producing dioctyl terephthalate by virtue of reactive distillation of waste polyester

    CN104722248A

  • Method for recovering terephthalic acid

    JP1994157402A

  • Production of aromatic dicarboxylic acid and alkylene glycol from polyester resin

    JP1994240046A

  • Production of high-purity isophthalic acid

    JP1995017901A

  • Method for producing purified terephthalic acid

    JP2004531573A